2015
DOI: 10.1021/acs.jpcc.5b02299
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo Jahn–Teller Origin of Buckling Distortions in Two-Dimensional Triazine-Based Graphitic Carbon Nitride (g-C3N4) Sheets

Abstract: Due to its direct band gap and light mass, the recently synthesized triazine-based, graphitic carbon nitride (TGCN) is considered a promising material for future microelectronics. However, despite the structural similarity with completely planar carbon-only graphene, TGCN sheets are different because of the presence of buckling distortions making the TGCN sheets nonplanar. In this article, we show that the sufficiently strong coupling between the unoccupied molecular orbitals (UMOs) with occupied molecular orb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 59 publications
4
35
0
1
Order By: Relevance
“…Closely spaced relevant occupied and unoccupied molecular orbitals that might vibronically couple along the b 2g distortion (the buckling mode) has been shown to be the origin of lowering of symmetry of Si 6 H 6 and Ge 6 H 6 from their planar D 6 h to puckered D 3 d point group 9. Similar lowering of symmetry has also been reported for larger two‐dimensional fragments of s‐triazenes 37. Nevertheless, intercalation of Ca II within the silicene layers is shown to quench the PJT distortion in the B(h) phase, thereby making the Si 6 rings perfectly planar (Figure 2 a,b).…”
Section: Resultssupporting
confidence: 57%
“…Closely spaced relevant occupied and unoccupied molecular orbitals that might vibronically couple along the b 2g distortion (the buckling mode) has been shown to be the origin of lowering of symmetry of Si 6 H 6 and Ge 6 H 6 from their planar D 6 h to puckered D 3 d point group 9. Similar lowering of symmetry has also been reported for larger two‐dimensional fragments of s‐triazenes 37. Nevertheless, intercalation of Ca II within the silicene layers is shown to quench the PJT distortion in the B(h) phase, thereby making the Si 6 rings perfectly planar (Figure 2 a,b).…”
Section: Resultssupporting
confidence: 57%
“…To analyze the chemical bonding pattern of the 2D‐B 4 P 2 sheet, the solid‐state adaptive natural density partitioning (SSAdNDP) algorithm was used . Previously it was shown that SSAdNDP is a powerful tool for analyzing chemical bonding in two‐dimensional periodic systems . A plane wave (PW) calculation was performed using 450 eV energy cut off with convergence threshold 10 −6 eV for total energy.…”
Section: Methodsmentioning
confidence: 99%
“…has attracted great interest. This is because of its unique chemical properties including large specific surface area, high adsorption capacity, and good electron conductivity, as well as its low price and good stability . Moreover, its nitrogen richness facilitates anchoring metal NPs …”
Section: Introductionmentioning
confidence: 99%
“…This is because of its unique chemical properties including large specific surface area, high adsorption capacity, and good electron conductivity, as well as its low price and good stability. 14,15 Moreover, its nitrogen richness facilitates anchoring metal NPs. 16 Compared with most of the other noble metals, the low-cost Pd catalysts exhibit similar or even better catalytic activity in many heterogeneous catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%